2023
DOI: 10.1002/jctb.7467
|View full text |Cite
|
Sign up to set email alerts
|

A combined experimental and computational approach for the rationalization of the catalytic activity of lipase B from Candida antarctica in water–organic solvent mixtures

Abstract: BackgroundThe addition of organic solvents to an aqueous medium for enzymatic reactions offers several advantages, as they can increase the solubility of substrates but can also lead to enzyme inactivation and/or aggregation.ResultsThe effect of adding 30% of several water‐soluble organic solvents on the catalytic activity of lipase B from Candida antarctica (CalB) was studied and the results showed that the highest activity was obtained with the addition of t‐butanol. t‐Butanol and acetonitrile were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…This is in line with the kinetic model used in the literature for modelling the reaction system. 44,45 The estimated parameters and 95% confidence intervals computed by the standard bootstrapping technique for the MM model are shown in Table 4. It can be observed that reaction rate model discrimination using the extent-based incremental identification presents an additional advantage for the proposed SSML approach if knowledge of the kinetic model is not available a priori .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with the kinetic model used in the literature for modelling the reaction system. 44,45 The estimated parameters and 95% confidence intervals computed by the standard bootstrapping technique for the MM model are shown in Table 4. It can be observed that reaction rate model discrimination using the extent-based incremental identification presents an additional advantage for the proposed SSML approach if knowledge of the kinetic model is not available a priori .…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with the kinetic model used in the literature for modelling the reaction system. 44,45 The estimated parameters and 95% confidence intervals computed by the standard bootstrapping technique for the MM model are shown in Table 4. It can be observed that…”
Section: Lipase-catalysed Hydrolysis Reactionmentioning
confidence: 99%